PROCESSES OF TRANSFORMATIONS: TRENDS OF ATOMIZATION AND HUMANIZATION - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2025)
The growth of prerequisites for the processes of atomization and humanization can produce results that differ significantly from each other. On the one hand, the development of essential forces, self-absorption, and self-knowledge can dominate, which is quite compatible with the development and humanization of the surrounding world. On the other hand, alienation can intensify and generalize social processes, with the prevalence of disunity, loneliness, and the “Homo homini lupus est” approach, when atomization and humanization directly conflict with each other. As is known, social atomization itself can become part of an environment that alienates a person, when larger units: cultures, communities, or families – are broken down into subcomponents, whose potential and dynamics are revealed in the process of the disintegration of relations in the cultural-civilizational world [1-8].